Synergies between space telescopes in the photometric characterization of the atmospheres of Hot Jupiters. Issue 4 (8th May 2019) - Singh, Vikash; Scandariato, G; Pagano, I
ABSTRACT: Previous generation of instruments has the opportunity to discover thousands of extra-solar planets, and more will come with the current and future planet-search missions. In order to go one step further in the characterization of exoplanets, in this paper we describe a way to compare the photometric observation of Hot Jupiters done with space telescopes such as HST, CHEOPS, TESS, PLATO, and JWST and give the first-hand characterization on their atmospheres. We analyse a set of planetary systems hosting a Hot Jupiter for which an atmospheric template is available in literature. For each system, we simulate the transit light curves observed by different instruments, convolving the incoming spectrum with the corresponding instrumental throughput. For each instrument, we thus measure the expected transit depth and estimate the associated uncertainty. Finally, we compare the transit depths as seen by the selected instruments and we quantify the effect of the planetary atmosphere on multiband transit photometry. We also analyse a set of simulated scenarios with different stellar magnitudes, activity levels, transit durations, and atmospheric templates to find the best cases for this kind of observational approach. We find in general that current and especially future space telescopes provide enough photometric precision to detect significant differences between the transit depths at different wavelengths. In particular, we find that the chromatic effect due to the atmosphere of the Hot Jupiters is maximized at later spectral types, and that the effect of stellar activity is smaller than the measurement uncertainties.